Humanitarian disarmament : an historical enquiry / Treasa Dunworth. - Dunworth, Treasa Moira (Cambridge studies in international and comparative law ;, 2020)
The humanitarian framing of disarmament is not a novel development, but rather represents a re-emergence of a much older and long-standing sensibility of humanitarianism in disarmament. The Book rejects the 'big bang' theory that presents the Anti-Personnel Landmines Convention 1997, and its successors - the Convention on Cluster Munitions 2008, and the Treaty on the Prohibition of Nuclear Weapons 2017 - as a paradigm shift from an older traditional state-centric approach towards a more progressive humanitarian approach. It shows how humanitarian disarmament has a long and complex history, which includes these treaties. This book argues that the attempt to locate the birth of humanitarian disarmament in these treaties is part of the attempt to cleanse humanitarian disarmament of politics, presenting humanitarianism as a morally superior discourse in disarmament. However, humanitarianism carries its own blind spots and has its own hegemonic leanings. It may be silencing other potentially more transformative discourses.